Human Extravillous Trophoblasts Require SRC-2 for Sustained Viability, Migration, and Invasion - Vineet K. Maurya; Pooja Popli; Bryan C. Nikolai; David M. Lonard; Ramakrishna Kommagani; Bert W. O’Malley; John P. Lydon (Cells)
Defective placentation is a recognized etiology for several gestational complications that include early pregnancy loss, preeclampsia, and intrauterine growth restriction. Sustained viability, migration, and invasion are essential cellular properties for embryonic extravillous trophoblasts to execute their roles in placental development and function, while derailment of these cellular processes is linked to placental disorders. Although the cellular functions of extravillous trophoblasts are well recognized, our understanding of the pivotal molecular determinants of these functions is incomplete. Using the HTR-8/SVneo immortalized human extravillous trophoblast cell line, we report that steroid receptor coactivator-2 (SRC-2), a coregulator of transcription factor-mediated gene expression, is essential for extravillous trophoblast cell viability, motility, and invasion. Genome-scale transcriptomics identified an SRC-2-dependent transcriptome in HTR-8/SVneo cells that encodes a diverse spectrum of proteins involved in placental tissue development and function. Underscoring the utility of this transcriptomic dataset, we demonstrate that WNT family member 9A (WNT 9A) is not only regulated by SRC-2 but is also crucial for maintaining many of the above SRC-2-dependent cellular functions of human extravillous trophoblasts.